Faith-Based Political Communication in Mandailing Natal’s Regional Elections - Azhar, Anang Anas; Santoso, Puji; Muhammad, Qasem (Jurnal Ilmiah Peuradeun, 2025)
This study examined the role and strategies of ulama in political communication during the regional elections (Pilkada) in Mandailing Natal Regency, Indonesia—a region where religious authority plays a central role in shaping political behavior. This research adopted a qualitative descriptive approach, utilizing in-depth interviews, which were selected purposefully for their active involvement in the local political landscape. Apart from that, observation and documentation were also used as data sources. Data were analyzed thematically using NVivo 12 Plus software. The findings revealed that ulama, as trusted religious figures, conveyed political messages through traditional religious forums such as majelis taklim and Friday sermons, as well as through digital platforms like WhatsApp and Facebook. These messages, rooted in Islamic values, emphasized leadership integrity, justice, and civic responsibility. The ulama’s communication strategy, which blended religious authority with cultural symbolism, significantly influences voter perceptions and participation. This study also highlighted the risk of social polarization when the ulama acts as partisan figures. This research contributes to the growing body of literature on religion and politics by offering insights into the symbolic and practical dimensions of faith-based political communication in Muslim-majority contexts. It also underscores the importance of ethical boundaries to ensure that religious leadership strengthens democratic engagement rather than undermining social cohesion.